Ingerencje Františka Ladislava Čelakovskiego w grafię fragmentów Psałterza floriańskiego - Balowski, Mieczysław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The author analyzes the graphics of the Florian Psalter used by the Czech Slavist František Ladislav Čelakovský, indicating the changes he made. The inclusion of this Polish language monument in the Czech edition of the Slavic chrestomathy section devoted to the Polish language was dictated by a practical purpose. The founding of the Department of Slavic Philology at the then University of Wrocław by F.L. Čelakovský forced the newly appointed professor to prepare teaching materials not only for teaching Polish, but also for teaching historical grammar of the Polish language. The popularity at that time of the newly discovered Polish Psalter and the imprecision of statements about the language of the Puławy Psalter forced Čelakovský to base his teaching process on the Florian Psalter. At the same time, taking into account the structure of students of Slavic studies in Wrocław, he was forced to take into account the specificity of the glottodidactic process.